Goethe yearbook : publications of the Goethe Society of North America. - Richter, Simon (Goethe Yearbook., 2005)
The 'Goethe Yearbook, ' first published in 1982, is a publication of the Goethe Society of North America and is dedicated to North American Goethe Scholarship. It aims above all to encourage and publish original English-language contributions to the understanding of Goethe and other authors of the 'Goethezeit, ' while also welcoming contributions from scholars around the world. This year's volume features a cluster of exceptional essays that shed new light on Goethe's 'Wilhelm Meister' novels and 'Faust, ' as well as fascinating articles on the early play 'Das Jahrmarktsfest zu Plundersweilen' and the poem 'Ilmenau, ' Schiller's 'Die Räuber, ' and an essay that places Goethe's thought in relation to current debates about cosmopolitanism and postcoloniality. Engaging reviews of recent publications in Goethe studies round out the volume. Contributors include Eric Denton, Matt Erlin, Jaimey Fisher, Ingrid Rieger, Rainer Kawa, David Barry, Stephanie Dawson, and John Pizer. Simon J. Richter is professor of German at the University of Pennsylvania. Book review editor Martha B. Helfer is professor of German at Rutgers University.